Words of Light : Theses on the Photography of History - Cadava, Eduardo (Book collections on Project MUSE., 1997)
Focusing on Walter Benjamin's discussions of the flashes and images of history, this book argues that the questions raised by this link between photography and history touch on issues that belong to the entire trajectory of Benjamin's writings.